Coltriciella multipileata (Agaricomycetes, Hymenochaetaceae), a new species from Mexico, related to ectomycorrhizal lineages - Valenzuela, Ricardo; Raymundo, Tania; Decock, Cony; Lara-Chávez, Ma Blanca Nieves; Luna-Vega, Isolda; García-Sandoval, Ricardo (Phytotaxa, 2020)
Coltriciella multipileata is described here as a new species from Mexico. The species grow on soils in open areas at the vicinity of living trees of Pinus patula, and its known only from the Parque Recreativo Los Colomos, Jalisco. The phylogenetic analysis based on partial nuclear 28S ribosomal DNA sequences, recovered Coltriciella multipileata as sister group with a specimen reported as ectomycorrhizal, and closely related with other two species that are considered saprophitic. According with our preliminary analysis of character states reconstruction, the ectomycorrhizal condition appeared early in the Coltriciella clade, with a high rate of transitions between ectomycorrhizal and saprophitic conditions. A key for species similar to Coltriciella multipileata is presented.